XIX ÁSIR AQÍRÍ – XX ÁSIR BASÍNDA ÁMIWDÁRYA BÓLIMINDEGI QAMAQXANALAR ISKERLIGINIŃ TARIYXÍY ANALIZI - Mamutov, Marat Mámbetmuratovich (SCIENCE and SOCIETY, 2026)
This article analyzes the prisons of the Amu-Darya department in the late 19th and early 20th centuries, their conditions, regulations, and the situation of the prisoners. The study reveals the organization of prisons in Chimbay and Petro-Aleksandrovsk (Turtkul), the activities of the prison administration and staff, as well as the role of prisons in the colonial policy of the Russian Empire.